PENGARUH LINGKUNGAN KERJA, DISIPLIN KERJA, DAN MOTIVASI TERHADAP KINERJA KARYAWAN DALAM SISTEM KERJA HYBRID PADA PT. RUANGGURU - Sahlah, Rifdatus; Utama, Rony Edward (Taksasila Edukasi Insani, 2026)
This study examines the effect of work environment, work discipline, and work motivation on employee performance within a hybrid work system at PT Ruang Raya Indonesia (Ruangguru). The implementation of hybrid work presents challenges in maintaining consistent employee performance due to differences in work settings and reduced direct supervision. This research employs a quantitative associative approach with saturated sampling involving 40 employees of the Kami Creative Production Division. Data were collected using questionnaires and analyzed through multiple linear regression with SPSS. The results show that the work environment has a positive but insignificant effect on employee performance, while work discipline and work motivation have a positive and significant effect.Keywords : employee performance, work environment, work discipline, work motivation, hybrid work system